DUSP5 promotes osteogenic differentiation through SCP1/2‐dependent phosphorylation of SMAD1. (10th July 2021) - Liu, Xuejiao; Liu, Xuenan; Du, Yangge; Hu, Menglong; Tian, Yueming; Li, Zheng; Lv, Longwei; Zhang, Xiao; Liu, Yunsong; Zhou, Yongsheng; Zhang, Ping
Abstract: Dual‐specificity phosphatases (DUSPs) are defined by their capability to dephosphorylate both phosphoserine/phosphothreonine (pSer/pThr) and phosphotyrosine (pTyr). DUSP5, a member of DUSPs superfamily, is located in the nucleus and plays crucially regulatory roles in the signaling pathway transduction. In our present study, we discover that DUSP5 significantly promotes osteogenic differentiation of mesenchymal stromal cells (MSCs) by activating SMAD1 signaling pathway. Mechanistically, DUSP5 physically interacts with the phosphatase domain of small C‐terminal phosphatase 1/2 (SCP1/2, SMAD1 phosphatases) by the linker region. In addition, we further confirm that DUSP5 activates SMAD1 signaling through a SCP1/2‐dependent manner. Specifically, DUSP5 attenuates the SCP1/2‐SMAD1 interaction by competitively binding to SCP1/2, which is responsible for the SMAD1 dephosphorylation, and thus results in the activation of SMAD1 signaling. Importantly, DUSP5 expression in mouse bone marrow MSCs is significantly reduced in ovariectomized (OVX) mice in which osteogenesis is highly passive, and overexpression of Dusp5 via tail vein injection reverses the bone loss of OVX mice efficiently. Collectively, this work demonstrates that the linker region of DUSP5 maybe a novel chemically modifiable target for controlling MSCs fate choices and for osteoporosis treatment. Abstract : DUSP5 promotes the osteogenic differentiation of mesenchymal stromal cells (MSCs) by repressing SMAD1 signaling pathway in a SCP1/2‐dependent manner. The linker region of DUSP5 occupies the phosphatase domain of SCP1/2 and thereby releases the inhibitory effect of SCP1/2 on SMAD1 signaling. Additionally, Dusp5 overexpression could effectively ameliorate osteopenia of mice.